The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The International Handbooks of Museum Studies 2015
DOI: 10.1002/9781118829059.wbihms992
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in the History Museum

Abstract: Research into communication strategies in museums and galleries has focused mainly on visitors’ learning and their cognitive responses. However, our thoughts and ideas are mediated through our emotions, which are historically and culturally situated. Using case studies, this chapter seeks to open a discussion about the place of emotions in museums. Focusing in particular on the discipline of history and history museums, it suggests that we need to pay more attention to affect and the emotions generated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This perspective is in congruence with psychological research that suggests that cognitive and affective aspects of empathy are interdependent, defining it as a process of understanding and emotionally responding to the thoughts and feelings of others (Hoffman 1984). It also resonates with recent insights of museum studies, in which interrelations of reason and emotion and the notion that emotional responses are shaped by people's cultural backgrounds have similarly been emphasised (Watson 2015). Smith's (2011) notion of registers of engagement attempts to give justice to the whole spectrum of ideological and affective visitors' responses as well as to the intensity of their engagement in museums.…”
Section: Historical Empathysupporting
confidence: 68%
“…This perspective is in congruence with psychological research that suggests that cognitive and affective aspects of empathy are interdependent, defining it as a process of understanding and emotionally responding to the thoughts and feelings of others (Hoffman 1984). It also resonates with recent insights of museum studies, in which interrelations of reason and emotion and the notion that emotional responses are shaped by people's cultural backgrounds have similarly been emphasised (Watson 2015). Smith's (2011) notion of registers of engagement attempts to give justice to the whole spectrum of ideological and affective visitors' responses as well as to the intensity of their engagement in museums.…”
Section: Historical Empathysupporting
confidence: 68%
“…As has been demonstrated by Yaniv Poria (2003), Smith (2006Smith ( , 2011 and Elasaid Munro (2013), museums are clearly places where people go not just to learn but also to feel. Similarly, the works of Sheila Watson (2015), and Kate Gregory and Andrea Witcomb (2007) have demonstrated that emotions are central to processes of learning and visitor engagement. Visitors in this study often used highly emotive language when relating material to their life.…”
Section: Resultsmentioning
confidence: 92%
“…In museum and heritage studies it has now been argued that it is impossible to understand why people visit museums and engage with heritage if emotions are not considered (Smith 2006;Gregory and Witcomb 2007;Watson 2015;Smith and Campbell 2016). Visitors were seen as active consumers and producers of emotions in museums, not vessels to be filled with information (Bangall 2003, 87).…”
Section: Introductionmentioning
confidence: 99%
“…Visitors were seen as active consumers and producers of emotions in museums, not vessels to be filled with information (Bangall 2003, 87). Emotions, thus, became understood as central in heritage-making in terms of how visitors were both engaging and disengaging with emotions (Gregory and Witcomb 2007;Smith 2006Smith , 2010Smith , 2015Smith , 2016Watson 2015Watson , 2016Smith and Campbell 2016;Dudley 2017). The sensory nondiscursive level and how affect is provoked by the museum atmosphere was also understood as interwoven in the museum experience (Gregory and Witcomb 2007;Witcomb 2013;Schorch 2014; Tolia-Kelly, Waterton and Watson 2017; de Jong 2018).…”
Section: Introductionmentioning
confidence: 99%